Religious Dance and Spiritual Connectivity in Yazidi Ritual Practices (Raparin Journal of Humanities (RJH), 2025)
This study is a descriptive, historical, and field-based investigation into the essence of Sema and the religious rituals of the Yazidi faith. It posits that these elements are integral to the experiential life of worship and spiritual connection among the Yazidis. Sema inherently contributes to the stimulation of the spirit and psyche and facilitates the unification of the religious community. It strengthens communal ties, enabling believers to transcend worldly limits, access spiritual realms, and establish direct connections with sacred entities.The objective of this research is to identify and define the roles and responsibilities associated with the essence of Sema from religious, cultural, and musical perspectives. It examines the place of music in defining the identity of various types of Sema. The outcomes of this study address the functions and roles of Sema and its essence within the cultural and religious framework, linking to traditions and customs. It explores how values and rituals are transmitted, reporting on identity and social action for succeeding generations through the promotion of spirituality, which fosters emotions and solidarity, supports the community, and engages with divine aspects, enhancing the community’s resilience and coherence. Each Sema has its own unique melody and rhythm, with music playing a pivotal role in defining the types of Sema within the religious community. These aspects constitute another dimension of the results of this research.